Digital Droplet PCR for SARS-CoV-2 Resolves Borderline Cases. Issue 6 (5th April 2021) - Xu, Jing; Kirtek, Timothy; Xu, Yan; Zheng, Hui; Yao, Huiyu; Ostman, Emily; Oliver, Dwight; Malter, James S; Gagan, Jeffrey R; SoRelle, Jeffrey A
Abstract: Objectives: The Bio-Rad SARS-CoV-2 ddPCR Kit (Bio-Rad Laboratories) was the first droplet digital polymerase chain reaction (ddPCR) assay to receive Food and Drug Administration (FDA) Emergency Use Authorization approval, but it has not been evaluated clinically. We describe the performance of ddPCR—in particular, its ability to confirm weak-positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) results. Methods: We clinically validated the Bio-Rad Triplex Probe ddPCR Assay. The limit of detection was determined by using serial dilutions of SARS-CoV-2 RNA in an artificial viral envelope. The ddPCR assay was performed according to the manufacturer's specifications on specimens confirmed to be positive (n = 48) or negative (n = 30) by an FDA-validated reverse transcription–polymerase chain reaction assay on the m2000 RealTime system (Abbott). Ten borderline positive cases were also evaluated. Results: The limit of detection was 50 copies/mL (19 of 20 positive). Forty-seven specimens spanning a range of quantification cycles (2.9-25.9 cycle numbers) were positive by this assay (47 of 48; 97.9% positive precent agreement), and 30 negative samples were confirmed as negative (30 of 30; 100% negative percent agreement). Nine of 10 borderline cases were positive when tested in triplicate. Conclusions: The ddPCR of SARS-CoV-2 is an accurate method, with superior sensitivity for viral RNA detection. It could provide definitive evaluation of borderline positive cases or suspected false-negative cases.